The Relationship Between Knowledge and Motivation About The Use of Dentures in Participants of Posbindu Melati Gunung Village South Jakarta - yani, Helda; Magdalena Tetelepta, Marzia; Ika Suwandari, Defi (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2024)
According to the World Health Organization (WHO) conveyed in The World Oral Health Report that the level of awareness of the Indonesian population in caring for dental and oral hygiene is not good so that there are 90% of individuals who have oral health problems and an increase in the prevalence of edentulous / tooth loss reaching 24%. tooth loss that is too long, can also cause a decrease in alveolar bone in edentulous areas, decreased masticatory function to speech disorders and can also affect the temporomandibular joint. Some data mention the lack of knowledge and motivation to use dentures. The study aimed to determine the relationship between knowledge and motivation for using and maintaining dentures for health at the Melati Posbindu RW.06 gunung village. This type of research is quantitative with a cross-sectional research design. The research sample was participants of Posbindu Melati RW 06, Gunung sub-district, using a purposive sampling method that met the sample inclusion criteria, totaling 30 respondents. The inclusion criteria for this study were participants aged ≥ 15 years and willing to be respondents, with exclusion criteria for respondents with severe oral disease and mental disorders. Analyzed using the Spearman rank correlation analysis statistical test with SPSS 25. The results of the research conducted obtained the results of the Spearman Rank Correlation analysis that the results of the significance of the relationship were known to have a significance value or sig. (2-tailed) of p value 0.000 with a magnitude of the relationship between the knowledge variable and motivation of 0.881. It can be concluded that there is a very strong relationship between knowledge and motivation to use and care for dentures for health at Posbindu Melati RW 06, Pegunungan Village in 2023.